Akhlaq Islami dan Hukum: Pilar Utama dalam Membangun Masyarakat Madani: Akhlaq Islami dan Hukum serta Masyarakat - Sarwo Edy; Septiayu R Wulandari (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This study employs thematic analysis to identify the main themes in the implementation of Islamic law within the framework of secular law. Legal institutions such as Sharia courts and fatwa councils play a significant role, although they create a dual legal system that can lead to confusion. Implementation challenges include differences in interpretation, resistance from secular groups, and limited resources. Social and cultural dynamics also affect the acceptance of Islamic law, with greater resistance in heterogeneous societies and the influence of globalization promoting secular values. Politics also plays a significant role, with conservative governments tending to support broader implementation of Islamic law, while liberal governments uphold secular principles. The research indicates that Islamic law is often partially integrated into secular legal systems, particularly in countries like Indonesia and Malaysia, with institutions such as Sharia courts and fatwa councils playing crucial roles, despite facing implementation challenges like differing interpretations and resistance from secular groups. The study also identifies challenges in applying religious values in modern life, such as conflicts with secular values, the influence of media and technology, lack of religious education, social pressures, the complexity of modern life, and economic challenges. The integration of moral values in formal education is carried out through subjects, extracurricular activities, and the role of teachers as moral exemplars. Keywords: Islamic ethics, Law, Civil society, Moral conduct, Social cohesion